1287. Understanding Factors Associated with Polypharmacy and Differential Medication Adherence in People with HIV. (15th December 2022) - Schwartz, Rebecca M; Charlton, Jessica; Gorlin, Margaret; Weinberg, Amy; Wallach, Frances; McGowan, Joseph
Abstract: Background: For people with HIV (PWH), number of chronic medications (meds) used to treat comorbidities may impact quality of life (QoL), illness perception, medication beliefs, and clinical outcomes. Factors associated with adherence to antiretrovirals (ARVs) may differ from adherence to other chronic meds. This study aims to assess these factors to promote better med management and adherence among PWH taking chronic meds and ARVs. Methods: 174 participants (pts) were enrolled from an HIV program in a large health system. Inclusion criteria were age > 18 years, English speaking, prescribed ARVs, and having > 1 comorbidity requiring a chronic med (non-ARV). Measures included validated scales of QoL, illness perceptions, med beliefs, and adherence barriers (e.g., forgot, too many pills, avoiding side effects); and past 6-month emergency department (ED) use and hospitalization. Generalized linear models, ANOVA, and Wilcoxon sum rank tests assessed associations between number of chronic meds (< 4 vs > 5) and outcomes. Multivariable logistic regression models using backwards elimination were used to assess factors associated with adherence (overall, HIV-meds, non-HIV meds). Results: Complete data from 160 pts were analyzed: 50% male; 84% US-born; 46% taking > 5 chronic meds. Pts taking > 5 meds were older, less likely to be employed, had significantly lower QoL (mean difference=5.23, 95%CI=0.19-10.27. p< .05), significantly higher med side effects (mean ranks=88.51 vs 73.77, p< .05), and 3-fold greater ED visits (mean estimate=2.99, 95%CI=1.52-5.89, p< .05). Regression models indicated that number of adherence barriers (but not other predictors) was consistently associated with lower adherence after controlling for demographics: (overall adherence: OR=0.85, 95%CI=0.79=0.91; HIV med adherence: OR=0.88, 95%CI=0.81-0.94; non-HIV med adherence: OR=0.86, 95%CI=0.80-0.92). Conclusion: Adverse events (i.e., ED use, poor QoL, med side effects) are associated with number of chronic meds. Number of adherence barriers is associated with poor adherence across med type, highlighting the importance of interventions to address polypharmacy and the complexities of managing HIV and comorbidities. Assessment of barriers can contribute to the promotion of adherence for both HIV and non-HIV meds. Disclosures: Amy Weinberg, DNP, MS, Gilead Sciences: Employee|Gilead Sciences: Stocks/Bonds.